A Theory-Based Contextual Nutrition Education Manual Enhanced Nutrition Teaching Skill - Kupolati, Mojisola D.; MacIntyre, Una E.; Gericke, Gerda J. (Frontiers in Public Health, 2018)
Background: A theory-based contextual nutrition education manual (NEM) may enhance effective teaching of nutrition in schools. School nutrition education should lead to the realization of such benefits as improved health, scholarly achievement leading to manpower development and consequently the nation’s development. The purpose of the study was to develop a contextual NEM for teachers of Grade 5 and 6 learners in the Bronkhorstspruit district, South Africa, and to assess teachers’ perception on the use of the manual for teaching nutrition. Methods: This descriptive case study used an interpretivist paradigm. The study involved teachers (N = 6) who taught nutrition in Life Skills (LS) and Natural Science and Technology (NST) in a randomly selected primary school in the Bronkhorstspruit district. Findings from a nutrition education needs assessment were integrated with the constructs of the Social cognitive theory (SCT) and the Meaningful learning model (MLM) and the existing curriculum of the Department of Basic Education (DoBE) to develop a contextual NEM. The manual was used by the teachers to teach nutrition to Grades 5 and 6 learners during the 2015 academic year as a pilot project. A focus group discussion was conducted with teachers to gauge their perceptions of the usefulness of the NEM. Data were analyzed using the thematic approach of the framework method for qualitative research. Results: Teachers described the NEM as rich in information, easy to use and perceived the supporting materials and activities as being effective. The goal setting activities contained in the NEM were deemed to be ineffective. Teachers felt that they did not have enough time to teach all the important things that the learners needed to know. Conclusion: Teachers perceived the NEM as helpful towards improving their nutrition teaching skills. The NEM template may furthermore guide teachers in planning theory-based nutrition lessons.